1999
DOI: 10.1007/s002030050681
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive, viable-colony staining method using Nile red for direct screening of bacteria that accumulate polyhydroxyalkanoic acids and other lipid storage compounds

Abstract: The oxazine dye Nile blue A and its fluorescent oxazone form, Nile red, were used to develop a simple and highly sensitive staining method to detect poly(3-hydroxybutyric acid) and other polyhydroxyalkanoic acids (PHAs) directly in growing bacterial colonies. In contrast to previously described methods, these dyes were directly included in the medium at concentrations of only 0.5 microgram/ml, and growth of the cells occurred in the presence of the dyes. This allowed an estimation of the presence of PHAs in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
406
1
9

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 658 publications
(417 citation statements)
references
References 26 publications
1
406
1
9
Order By: Relevance
“…The N-limit media showed more number of PHB granules than the P-limit media. The reports says that this viable-colony staining method was in particular applicable to gram-negative bacteria and it was less suitable for discriminating between PHAnegative and PHA-positive strains of grampositive bacteria such as Bacillus megaterium or Rhodococcus ruber (Spiekermann et al, 1999). But our studies show the presence of PHB in all the five positive strains and it was confirmed by FTIR and NMR analysis.…”
Section: Screening Of Phb Producing Microorganismsmentioning
confidence: 52%
See 1 more Smart Citation
“…The N-limit media showed more number of PHB granules than the P-limit media. The reports says that this viable-colony staining method was in particular applicable to gram-negative bacteria and it was less suitable for discriminating between PHAnegative and PHA-positive strains of grampositive bacteria such as Bacillus megaterium or Rhodococcus ruber (Spiekermann et al, 1999). But our studies show the presence of PHB in all the five positive strains and it was confirmed by FTIR and NMR analysis.…”
Section: Screening Of Phb Producing Microorganismsmentioning
confidence: 52%
“…Bright orange fluorescing PHB granules were more prominent in Bacillus sphaericus NII 0838. The Nile blue stain binds specifically to PHB granules and they fluoresce with orange color under excitation wavelength of 390 nm (Spiekermann et al, 1999). The N-limit media showed more number of PHB granules than the P-limit media.…”
Section: Screening Of Phb Producing Microorganismsmentioning
confidence: 99%
“…Positive yeast colonies containing the designated plasmid pBK/PHB were screened for PHB expression using the Nile-Red staining assay (Spiekermann, et al, 1999). It is known that the Nile-red stain emitted strongly positive red fluorescence signals only with hydrophobic compounds like PHAs and lipids.…”
Section: Discussionmentioning
confidence: 99%
“…A cassette including the three genes of the PHA biosynthesis pathway of Ralstonia eutropha {beta-ketothiolases (phbA); NADPH-linked-acetoacetyl-CoA reductase (phbB) and PHA synthase (phbC)} was obtained from the plasmid pBHR68 (pBluscriptSK -) that contains a 5.2 Kb fragment from chromosomal DNA of Ralstonia eutropha (Spiekermann, et al, 1999). Subsequently, the cassette was digested with endonucleases enzymes Xba1 and BamHI and subcloned by ligation into the pBK-CMV phagemid vector (Stratagene, La Jolla, CA, USA).…”
Section: Construction Of An Episomal Vectormentioning
confidence: 99%
See 1 more Smart Citation